2016
DOI: 10.1515/sgem-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Geotextile Reinforcement on Shear Strength of Sandy Soil: Laboratory Study

Abstract: This paper presents results of a series of undrained monotonic compression tests on loose sand reinforced with geotextile mainly to study the effect of confining stress on the mechanical behaviour of geotextile reinforced sand. The triaxial tests were performed on reconstituted specimens of dry natural sand prepared at loose relative density (Dr = 30%) with and without geotextile layers and consolidated to three levels of confining pressures 50, 100 and 200 kPa, where different numbers and different arrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Geogrid is a geosynthetic material used as reinforcement in construction works, which increases the bearing capacity and equalizes displacements in sand conditions. [1][2][3][4] Geogrid typically includes a mixture of polypropylene (PP), high-density polyethylene (HDPE), and polyester (PET). Geogrid can be either flexible or rigid in nature; the manufacturing process, manufacturing technology, and the behavior of grids will vary depending on the type of synthetic materials used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geogrid is a geosynthetic material used as reinforcement in construction works, which increases the bearing capacity and equalizes displacements in sand conditions. [1][2][3][4] Geogrid typically includes a mixture of polypropylene (PP), high-density polyethylene (HDPE), and polyester (PET). Geogrid can be either flexible or rigid in nature; the manufacturing process, manufacturing technology, and the behavior of grids will vary depending on the type of synthetic materials used.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained reveal that a high value of confining pressure can restrict the sand dilatancy when shearing. [4] A series of consolidated undrained triaxial compression tests for investigating the shear behavior of geotextilereinforced clay were conducted. The experimental results revealed that during consolidation, non-woven geotextile as a permeable material reduced the time of consolidation; however, it induced a higher volume change.…”
Section: Introductionmentioning
confidence: 99%
“…Several works have been carried out in the laboratory on soil samples to study the influence of the addition of reinforcement under several types and forms on the behavior of the soil. [14,15,21,22,24,30,36] Reinforcing soils using tension resisting elements is an attractive means of improving the performance of soil in a cost effective manner. The use of random discrete flexible fibers mimics the behavior of plants roots of surface vegetation and contribute to the stability of soil mass by adding strength to the near-surface soils in which the effective stress is low.…”
Section: Introductionmentioning
confidence: 99%
“…One plausible reason would be that the increasing number of geotextile layers may have caused the cohesion of reinforced soil to increase due to the layers having interlocked with the soil particles, thus having reduced the number of contact points between the soil grains [58]. The increase in cohesion would have led to a corresponding increase in both the elastic modulus and undrained shear strength parameters of the soil.…”
Section: Elastic Modulus and Undrained Shear Strength Parametersmentioning
confidence: 99%